Yersinia ironomics: comparison of iron transporters among Yersinia pestis biotypes and its nearest neighbor, Yersinia pseudotuberculosis - Stanislav Forman; James T. Paulley; Jacqueline D. Fetherston; Yi-Qiang Cheng; Robert D. Perry (BioMetals, 2010)

Insights into Yersinia pestis biofilm development: topology and co‐interaction of Hms inner membrane proteins involved in exopolysaccharide production - Alexander G. Bobrov; Olga Kirillina; Stanislav Forman; Dietrich Mack; Robert D. Perry (Environmental Microbiology, 2008)
Summary Primarily, three operons, hmsHFRS, hmsT and hmsP , are responsible for the development of a Yersinia pestis biofilm, which is essential for blockage‐dependent transmission of plague from fleas to mammals. Here, using specific antibodies, a polymeric β‐1,6‐ N ‐acetyl‐ d ‐glucosamine‐like polysaccharide was detected in the extracellular matrix of hmsHFRS ‐dependent Y. pestis biofilm. The production of this exopolysaccharide (EPS) was controlled by diguanylate cyclase HmsT and EAL domain phosphodiesterase HmsP, acting as positive and negative regulators respectively. Cellular compartmentalization of soluble segments of Hms inner membrane proteins, including the putative glycosyltransferase domain of HmsR, the diguanylate cyclase/GGDEF domain of HmsT and the phosphodiesterase/EAL domain of HmsP, was determined by a combination of topology prediction algorithms and construction of C‐terminal translational fusions with β‐galactosidase and alkaline phosphatase. Multiple interactions of Hms inner membrane proteins were detected using bacterial cAMP based two‐hybrid system. Biochemical analyses confirmed some of these protein–protein interactions. Our results indicate that synthesis and regulation of the Y. pestis biofilm EPS occurs in the cytoplasm by a proposed Hms enzymatic complex.